(Withdrawn)Detection of pathogens in waste water and soil by Taqman Array Card (TAC) system (Bangladesh Journal of Zoology, 2018)
25 August 2020Due to some unavoidable reasons the editorial board is willing to declare that the article entitled “Sarkar, F., Khanum, H., Zaman, R., Ahmed, T., Anik, M. K., and Haque, R. (2018). Detection of Pathogens in wastewater and soil by Taqman Array Card (TAC) system. Bangladesh Journal of Zoology. 46(2), 125-135 (http://dx.doi.org/10.3329/bjz.v46i2.39046) is withdrawn by the author. Therefore, after this declaration the authors will not have the privilege to use this article as an intellectual property quoting this journal.